La risposta istituzionale del governo Orbán alla pandemia da Coronavirus: dai poteri eccezionali alla revoca dello stato di pericolo: Il mondo e la lotta alla pandemia da COVID-19 (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
In order to react effectively to the COVID-19 pandemic, the Hungarian Government declared the state of danger on March 11th on the basis of article 53 of the Fundamental Law. On March 30th the National Assembly passed the Act No. XII of 2020 ‘On the containment of Coronavirus’ with a qualified majority providing the Government with the power to adopt exceptional measures and to amend existing Acts by means of a decree. The authorisation given to the Government is temporally limited: exceptional measures must be necessary and proportionate in the context of the COVID-19 pandemic to protect citizens’ lives, health, security and economic stability. The measures will cease to be in force when the state of danger ends. The special legal order has been revoked on June 18th.
Keywords: Hungary; Orbán; Coronavirus; special legal order; state of danger